Exploring determinants of antimicrobial prescribing behaviour: a qualitative study using the Theoretical Domains Framework. (1st April 2022) - Talkhan, H; Stewart, D; Mcintosh, T; Ziglam, H; Abdulrouf, P V; AL-HAIL, M; Diab, M; Cunningham, S
Abstract: Introduction: Few qualitative studies have explored determinants of antimicrobial prescribing behaviour in hospitals, and none has made reference to behavioural theories. An understanding of these determinants is required for the successful development and implementation of behaviour change interventions (BCIs) in this area. Aim: To explore the determinants of clinicians' antimicrobial prescribing behaviour, using the Theoretical Domains Framework (TDF; a framework of behavioural theories). Methods: This work was part of a multi-phase explanatory, sequential mixed methods PhD programme of research. This qualitative part involved semi-structured, online (video) interviews via a videoconferencing software programme (Zoom) with clinicians (doctors and pharmacists) based in 12 Hamad Medical Corporation hospitals in Qatar. Clinicians were sampled purposively in strata of gender, profession, years of experience and area of practice. The interview schedule was developed based on a review of published literature (1), previous findings of quantitative research (2) and the TDF to ensure comprehensive coverage of key determinants (including barriers and facilitators) related to clinicians' antimicrobial prescribing behaviour. Interviews were conducted from December 2020 to February 2021, audio-recorded, transcribed and independently analysed by two research team members using the TDF as an initial coding framework. Results: Data saturation was achieved after interviewing eight doctors and eight pharmacists from a range of areas of practices and with a variety of experiences. A number of themes, linked to ten TDF domains, were identified as determinants of antimicrobial prescribing behaviour and these determinants were interrelated. In-depth analysis identified several barriers and facilitators that may contribute to inappropriate or appropriate antimicrobial prescribing. Main barriers identified were around hospital guidelines and electronic system deficiencies (environmental context and resources), gaps in the knowledge in relation to guidelines and appropriate prescribing (knowledge), restricted roles/responsibilities of microbiologists and pharmacists (professional role and identity), uncomfortable antimicrobial prescribing decisions (memory, attention and decision processes), as well as professional hierarchies and poor multidisciplinary teamworking/relationships (social influences). "Sometimes, the barrier would be the ego of senior doctors who refuse our evidence-based recommendation and depend on their clinical judgement or experience" (Pharmacist 470, Cardiology). Key facilitators highlighted included guidelines compliance goals and intentions, and the beliefs of consequences of appropriate or inappropriate prescribing. Further education and training sessions, and some changes to guidelines, including accessibility were also considered essential. "We need to seriously consider getting an antibiotic guidelines app which is downloaded to clinicians' mobile phones. The mobile app is handy, you can access it anytime even at the patient's bedside" (Doctor 514, Microbiology). Conclusion: This qualitative study, using a theoretically based approach, has identified that antimicrobial prescribing in hospitals is a complex process influenced by a broad range of behavioural determinants that described specific barriers and facilitators. The in-depth understanding of this complexity provided by this phase of the research may contribute to the design and development of theoretically based BCIs to improve clinicians' antimicrobial prescribing. Limitations include data collected with online interviews due to the Covid-19 restrictions. This may have excluded some clinicians who did not feel comfortable with or have access to the technology required. References: (1) Talkhan H, Stewart D, Mcintosh T, Ziglam H, Abdulrouf P, Al-Hail M et al. The use of theory in the development and evaluation of behaviour change interventions to improve antimicrobial prescribing: a systematic review. Journal of Antimicrobial Chemotherapy. 2020;75(9):2394-2410. (2) Talkhan H, Stewart D, McIntosh T, Ziglam H, Abdulrouf P, Al-Hail M et al. Using the Theoretical Domains Framework to investigate clinicians' behavioural determinants of antimicrobial prescribing in Qatar. International Journal of Pharmacy Practice. 2021;29(1):i20-i22.